New species of Pisionidens (Sigalionidae, Annelida) from Akumal, México - Petersen, H. Cecilie B.; Gonzalez, Brett C.; Martínez, Alejandro; Worsaae, Katrine (Zootaxa, 2016)
Pisionidens Aiyar & Alikuhni, 1943 is a genus of small scale-less annelids formerly belonging to the family ‘Pisionidae’, now synonymized with the scale worm family Sigalionidae. A new species from Akumal, México, Pisionidens ixazaluohae n. sp., is herein described, including a genetic barcode, and diagnosed by parapodia from segment 8, males having a continuous line of midventral pores, and the presence of a single copulatory segment without parapodia. The new species differs in morphology from the three previously described species, including P. indica (Aiyar & Alikuhni, 1940), representing the only other species previously reported from the Caribbean Sea and Gulf of Mexico. A comparative table with a summary of the main taxonomic characters of all described species of the genus, including information on distribution, is provided.